Assessment of the indirect impact of wildfire (severity) on actual evapotranspiration in eucalyptus forest based on the surface energy balance estimated from remote-sensing techniques. Issue 20 (18th October 2018) - Häusler, Melanie; Nunes, João P.; Soares, Paula; Sánchez, Juan M.; Silva, João M. N.; Warneke, Thorsten; Keizer, Jan Jacob; Pereira, José M. C.
ABSTRACT: Wildfires have a strong impact on the environment, changing its structure, soil properties, and microclimate and subsequently its water cycle with implications on the surface energy fluxes. Persisting droughts and catastrophic forest fires initiated this case study of pure eucalyptus stands in north-central Portugal. Although many studies have investigated changes in actual evapotranspiration (ETa ), surface energy flux patterns, and the related physical parameters, only a few concentrated on the fire-driven changes in pure eucalyptus stands in the Mediterranean climate. This study aims to understand the consequences of wildfires on the water cycle, namely the ETa, and the surface energy heat fluxes by applying a simplified two-source energy balance model in combination with medium-resolution imagery (Landsat 8). A total of 21 different burnt locations were evaluated, which burned between 2011 and 2013. Estimated surface energy fluxes and daily ETa were compared to nearby control sites (unburnt) during satellite overpass for the time after the fire (2013–2015). The fire scars were classified into their burn severity, using the differenced Normalized Burn Ratio. The absolute difference of ETa ( ETa ) between unburnt and burnt locations was used to identify fire-driven changes in magnitude and its evolution over time. Our results show that for the unburnt stands, the contributions to the total latent heat flux were around 80% from the canopy and 20% from the soil, while for the burnt site the contributions were around 30% (canopy) and 70% (soil) shortly after the fire. Inter-annually, the difference in ETa increased during the rainy season, which was related to the epicormic shooting, the fast regrowth rate of foliage, and the abundance of water. Generally, smaller differences in ETa were related to the severity classification and stand properties (i.e. tree species and soil characteristics). Two to three years after the fire events, ETa became non-significant for all severity classes, leading to an impact on the total water cycle smaller in comparison to other post-fire studies.